Entwicklung und Wandlung der venezolanischen Kulturlandschaft unter der Herrschaft des Erdöles - Otremba, Erich (ERDKUNDE, 1954)
Beginning with a sketch of the tropical agricultural scence before the Great War the paper describes the development of the mineral oil economy from the year 1878, when the first bore hole was sunk, to the time when the 100 million cu. m. mark was passed. It discusses in detail the geological bases, the circumstances of production, and problems of communications and settlement of the two large oil provinces of which the one on Lake Maracaibo supplies two thirds and the other in the Oriente one third of the total production. On an average over the last few years, mineral oil made up 97 per cent, of the income from exports and at a maximum 70 per cent, of the public revenue. The direct results of the oil economy are to be seen in a planned opening up of the country by modern communications, an extraordinary urbanisation, which outpaces all attempts at planning, and industrialisation for the production of consumer goods, mainly concentrated in the area Caracas-Valencia. Side by side with the great efforts towards self-sufficiency in basic foodstuffs goes a considerable movement of people to the towns, which in parts of the Llanos and the peasant farming country of the Andes resulted in an actual population decrease. Since 1950 iron ore mining has come to the forefront, together with the oil economy. Mining is based on high quality haematites found in two centres in the region of the lower Caroni river. In the country these ores are considered a productive base for the fostering of an indigenous heavy industry, whereas oil is first of all a source of revenue for financing the building of towns and the development of a health service and education.